Integration of Quality Function Deployment (QFD) and Ergonomic Work Posture Analysis to Redesign the Dyeing Table at Batik Mahkota Laweyan - Muslimah, Etika; Choirunnisa, Hasna; Munawir, Hafidh; Danang Aryo Putro Satriono, Raden (Spektrum Industri, 2025)
The traditional batik industry still depends on non-ergonomic tools, especially during the Colet dyeing process, which exposes artisans to significant musculoskeletal disorder (MSD) risks. Prolonged static postures, repetitive arm movements, and mismatched table heights cause discomfort in the back, shoulders, and neck, ultimately reducing productivity. This study aims to design an ergonomic workstation that enhances safety and comfort for batik workers through the integration of the Nordic Body Map (NBM), Rapid Entire Body Assessment (REBA), and Quality Function Deployment (QFD) approaches. Three workers from Batik Mahkota Laweyan participated in the research through questionnaires, observations, and interviews. NBM identified the colet process as the most discomfort-inducing activity, while the initial REBA score of 9 indicated a very high ergonomic risk. The QFD analysis translated workers’ needs into specific technical criteria, such as adjustable height, tiltable surface, and lightweight materials, resulting in a redesigned dyeing table prototype. CATIA simulations validated the improvement, with the REBA score decreasing from 9 to 3, signifying a shift from high to low risk. The findings confirm that integrating ergonomic analysis tools with participatory design effectively reduces MSD risk and supports user-centered innovations in traditional craft industries. The study contributes theoretically by proposing a replicable framework that bridges ergonomic assessment and design application, and practically by providing a validated workstation design that improves comfort, health, and productivity. The novelty lies in the combined use of NBM, REBA, and QFD within a single methodological framework, an approach rarely applied in the traditional batik sector, demonstrating how systematic ergonomic integration can modernize artisanal practices while preserving cultural craftsmanship.